2020
DOI: 10.1101/2020.05.19.104273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial D-loop sequence variation and maternal lineage in the endangered Cleveland Bay horse

Abstract: Genetic diversity and maternal ancestry line relationships amongst a sample of 96 Cleveland Bay horses were investigated using a 479bp length of mitochondrial Dloop sequence. The analysis yielded at total of 11 haplotypes with 27 variable positions, all of which have been described in previous equine mitochondrial DNA dloop studies. Four main haplotype clusters were present in the Cleveland Bay breed describing 89% of the total sample. This suggests that only four principal maternal ancestry lines exist in the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, a survey of the 343‐bp fragment of the D‐loop region in 296 Thoroughbred horses 31 yielded 25 unique mitochondrial sequences at 42 polymorphic sites. Similarly, only 11 haplotypes were identified in the Cleveland Bay horse breed, four of which represented 89% of the sampled population 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a survey of the 343‐bp fragment of the D‐loop region in 296 Thoroughbred horses 31 yielded 25 unique mitochondrial sequences at 42 polymorphic sites. Similarly, only 11 haplotypes were identified in the Cleveland Bay horse breed, four of which represented 89% of the sampled population 40 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, only 11 haplotypes were identified in the Cleveland Bay horse breed, four of which represented 89% of the sampled population. 40 For our LRPCR-assayed samples, we identified 186 polymorphic sites across the mitochondrial genome, 29 of which lie in the D-loop region. The additional information gleaned shows the utility of the tiled LRPCR amplicon approach compared with a single, short-range product.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of European and Asian horse breeds revealed differentiated distribution of mtDNA haplogroup variants and evidence of a biogeographic wedge in Asian populations, including association of "Eastern" mtDNA types with haplogroups Q and R. Interestingly, these haplogroups were identified in horses of the Kabardian and Vyatskaya horse breeds bred in the European part of the Russian Federation (Khaudov et al, 2018;Khrabrova et al, 2020), but were absent in the Thoroughbred and Cleveland Bay horses created in England (Khrabrova et al, 2019;Dell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…
The need to manage inbreeding in closed populations of animals such as domestic pets, captive populations of wildlife, or farmed livestock has been further emerging in international policy through individual national efforts, as well as guidance from regulatory bodies such as the United Nations Farm Animal Organization. As gene sequencing technologies become more widespread and levels of inbreeding can now be assessed using runs of homozygosity (ROH) determined using single-nucleotide polymorphisms (SNPs), it has been suggested that pedigrees alone are no longer adequate to formulate breed management programs (Dell et al, 2020a).Conversely, it has been suggested that where a pedigree is deep, it may well remain the preferred tool to assist in formulating breed
…”
mentioning
confidence: 99%
“…management programs to control the rate of increase in inbreeding (Dell et al, 2020b), maximize effective population size (N e ), and limit the expression of deleterious alleles (Dell et al, 2020a(Dell et al, , 2020b.…”
mentioning
confidence: 99%